2010
DOI: 10.1007/s10409-010-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on correlation between turbulence and sound in a subsonic wind tunnel

Abstract: In this paper, the effects of turbulence on sound generation and velocity fluctuations due to pressure waves in a large subsonic wind tunnel are studied. A trip strip located at different positions in the contraction part or at one position in the diffuser of a large wind tunnel is used to investigate the aforementioned phenomenon, and the results indicate that the trip strip has significant effects on sound reduction. The lowest turbulence intensity and sound are obtained from a trip strip with a diameter of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Manshadi et al [16] carried out experimental work on the effects of turbulence generation and velocity fluctuations due to pressure waves in a large low-speed wind tunnel. The study experimentally investigated the relationship between turbulence and generation of sound waves.…”
Section: Previous Related Workmentioning
confidence: 99%
“…Manshadi et al [16] carried out experimental work on the effects of turbulence generation and velocity fluctuations due to pressure waves in a large low-speed wind tunnel. The study experimentally investigated the relationship between turbulence and generation of sound waves.…”
Section: Previous Related Workmentioning
confidence: 99%
“…The results of this research determine that while the share due to the monopole is dominant, the share due to the dipole and quadrupole remains less important. Furthermore, it is found that sound waves have a modest impact on the measured longitudinal turbulence and is essentially generated by eddies [11]. On the assumptions that first these sound waves are of plane type and contribute only to the u component and second that the turbulence and sound are statistically independent, Uberoi [12] has shown that the spatial correlation coefficient at two different points 1 and 2 for large separation of the points is defined by: …”
Section: The Important Parameters For Turbulence Measurementmentioning
confidence: 99%
“…These parameters are defined according to: The source of turbulence of wind tunnel may briefly divide in two parts; i.e., turbulence due to eddies (vortex shedding, boundary layer, shear stress, secondary flows) and noise (mechanical, vibration and aerodynamic) that There is a correlation between them. Manshadi et-al in [11] studied the effects of turbulence on the sound generation and velocity fluctuations due to pressure waves in a large subsonic wind tunnel. The results of this research determine that while the share due to the monopole is dominant, the share due to the dipole and quadrupole remains less important.…”
Section: The Important Parameters For Turbulence Measurementmentioning
confidence: 99%
See 2 more Smart Citations